Special Study on Benchmarking the Quality of Project Economic Analysis for the South Asia Region - Ezemenari, Kene; Ye, Xiao (World Bank, Washington, DC, 2017)
This paper benchmarks the quality of project economic analysis in South Asia against other World Bank regions, using data on project exits between 1975 and 2015. The results show that the South Asia region performs on par with the other regions, in that the share of project documents that report estimated economic rates of return have declined from 70 to 36 percent for South Asia and the other regions. This finding suggests there is less attention to project economic analysis (especially for sectors where this has been a traditional practice, such as energy, transport, water, and agriculture). The finding also indicates that the incidence of reporting rates of return in project documents and the dispersion or difference between rates of return estimated at project appraisal and completion are significantly correlated with project performance (after correcting for country- and project-level variables). For the project-level variables, the task team effect is a key variable that explains project outcomes. The paper discusses the implications of the analyses for strengthening project performance and risk mitigation.